Establishment of a TNFRSF11B knock-out human induced pluripotent stem cell line (KSCBi002-B-2) via CRISPR/Cas9 system - Jujin Jeong; Dahye Lee; Byeong-Cheol Park; Tae-Hoon Lee; Sang-Wook Park (Stem Cell Research, 2023)
A TNFRSF11B (TNF Receptor Superfamily Member 11b) gene encodes a soluble decoy receptor, osteoprotegerin (OPG), which has a key role in repressing osteoclast differentiation. In this report, we generated a biallelic knock-out hiPSC line for the TNFRSF11B gene via CRISPR/Cas9. When TNFRSF11B Knock-out hiPSCs were differentiated into mesenchymal progenitor cells (MPCs), the expression level of OPG was significantly decreased compared to normal hiPSC-derived MPCs. This knock-out hiPSCs will provide a chance to study Paget disease of bone 5 (juvenile Paget disease).